Occupational Therapy Occupation Focused Holistic Practice in Rehabilitation - Huri, Meral (IntechOpen, 2017)
This new book presents the growing occupational therapy knowledge and clinical practice. Occupational therapy, as a health profession, is concerned with preserving well-being through occupations, and its main goal is to help people participate in the activities of daily living. This is achieved by working with people to improve their ability to engage in the occupations they want to engage in or by changing the occupation or the environment to better support their occupational engagement. The topic of the book has been structured on occupational therapy framework and reflects new research, techniques, and occupational therapy trends. This useful book will help students, occupational therapy educators, and professionals to connect occupational therapy theories and the evidence-based clinical practice.